Trend of Cesarean Section Rates and Related Factors Among First-Time Mothers with Single Pregnancies in Zhejiang Province, China: Evidences from a Multi-Center Study - Liu B; Abdi MA; Ma Y (International Journal of Women's Health, 2025)
Bingqing Liu,* Mustafe Abdalle Abdi,* Yuanying Ma Women’s Hospital School of Medicine Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuanying Ma, Women’s Hospital, Zhejiang University School of Medicine, Xueshi Road 1, Hangzhou, Zhejiang Province, 310003, People’s Republic of China, Email mayuanying88@zju.edu.cnPurpose: The overuse of cesarean section (C-section) is a worldwide public health concern, the most effective measure lies in reducing the rate among primiparous women. We aimed to describe the trend, propose reference values and analyze risk factors of C-section among primiparous women in Zhejiang Province, China.Patients and Methods: We used data of China’s National Maternal Near-Miss Surveillance System from 2012 to 2021. The C-Model was used to calculate the reference values, and logistic regression analysis was employed to explore risk factors.Results: The C-section rate for primiparous women initially decreased and then rose again, the average rate was 36.1%, with a reference C-section rate of 11.8%. In addition to recognized indications for C-section, we also identified advanced maternal age (OR: 3.21, 95% CI: 3.08, 3.35), higher hospital level (OR: 1.15, 95% CI: 1.13, 1.17), higher education level [college or above: 1.05 (1.02, 1.07); high school: 1.1 (1.08, 1.13)], history of abortion (OR: 1.30, 95% CI: 1.28, 1.32), and male infant (OR: 1.15, 95% CI: 1.13, 1.16) as independent risk factors.Conclusion: Reducing the C-section rate for primiparous women by two-thirds was possible in Zhejiang. Systemic health policies were urgently needed to further reduce the C-section rate.Keywords: maternal, C-section, reference C-section rate, C-model, risk factors